Elizabethkingia Anophelis and Miricola in El Salvador: Report of the first three cases - Flor Castro-Rodriguez; Carmen Albanez-Ayala; Yakdiel Rodriguez-Gallo; Rodrigo Amaya-Reyes; Alfredo Merino-Luna (IDCases)
Elizabethkingia spp. is an emerging bacterium posing a global threat, causing potentially fatal infections often associated with high mortality rates. This study reports the first three patients with Elizabethkingia Anophelis and Miricola infections in El Salvador, Central America. Cultures conducted using MALDI-TOF MS Biotyper technology confirmed the presence of these pathogens. The method of infection in the patients is still unclear, although in one of them, it could have been through nosocomial transmission. In the other two patients, transmission through mosquitoes, endemic to the region, is not ruled out. Efforts to prevent and enhance the understanding of infections caused by Elizabethkingia spp., as well as to restrict their spread, must be effectively intensified in the face of this new challenge.